Clinical and Pathophysiological Insights Into Immunological Mediated Glomerular Diseases in Childhood - Mastrangelo, Antonio; Serafinelli, Jessica; Giani, Marisa; Montini, Giovanni (Frontiers in Pediatrics, 2020)
The kidney is often the target of immune system dysregulation in the context of primary or systemic disease. In particular, the glomerulus represents the anatomical entity most frequently involved, generally as the expression of inflammatory cell invasion or circulant or in situ immune-complex deposition. Glomerulonephritis is the most common clinical and pathological manifestation of this involvement. There are no universally accepted classifications for glomerulonephritis. However, recent advances in our understanding of the pathophysiological mechanisms suggest the assessment of immunological features, biomarkers, and genetic analysis. At the same time, more accurate and targeted therapies have been developed. Data on pediatric glomerulonephritis are scarce and often derived from adult studies. In this review, we update the current understanding of the etiologic events and genetic factors involved in the pathogenesis of pediatric immunologically mediated primitive forms of glomerulonephritis, together with the clinical spectrum and prognosis. Possible new therapeutic targets are also briefly discussed.